Parent–child relationships and child executive functioning at school entry: the importance of fathers. Issue 5 (16th April 2019) - Hertz, Sarah; Bernier, Annie; Cimon-Paquet, Catherine; Regueiro, Sophie
ABSTRACT: This study aimed to examine the unique and interactive contributions of the quality of mothers' and fathers' relationships with their toddlers to the prediction of children's subsequent executive functioning (EF). The sample included 46 low-risk middle-class families. The quality of mother–child and father–child interactions was assessed independently during separate interactive sequences at 18 months. Child EF problems were reported by teachers in kindergarten. The results indicated that only father–child interactions made a unique contribution to the prediction of children's EF, and no interaction effect was observed. Kindergarteners who benefited from higher quality interactions with their fathers in toddlerhood were considered by their teachers to present fewer EF problems in everyday school situations. These results appeared to be somewhat more pronounced in father–son than father–daughter dyads. Overall, the results suggest that fathering and father–child relationships may deserve more empirical attention than they have received thus far in the EF literature.